Implementation of Syndromic Surveillance Systems in Two Rural Villages in Senegal - Abat, Cédric; Colson, Philippe; Chaudet, Hervé; Rolain, Jean-Marc; Bassene, Hubert; Diallo, Aldiouma; Mediannikov, Oleg; Fenollar, Florence; Raoult, Didier; Sokhna, Cheikh (PLOS Neglected Tropical Diseases, 2016)
Author Summary Infectious diseases are still a major public health problem for humanity, especially because of their unpredictability. In this context, developing surveillance systems is one of the most effective solutions to fight them, including in Sub-Saharan African countries where the situation is particularly worrying. This study describes how automated surveillance systems have been implemented in two rural areas in Senegal for the weekly surveillance of 15 pathogens responsible for fever in Africa and on the basis of laboratory data from two rural laboratories. In addition, the first results of this surveillance are presented. The two surveillance systems prospectively and retrospectively detected several abnormal events, and allowed us to observe that the distribution of the pathogens was not the same depending on the region under surveillance. This study provides evidence on the possibility of developing surveillance systems in rural areas in Africa. Such initiatives are needed, especially to improve our global knowledge on infectious diseases in this continent.